Technical and economic feasibility of sensor technology for health/environmental condition monitoring - Karim, A.N. Mustafizul; Nordin, Anis Nurashikin; Begum, Shahida (Elsevier, 2014)
Continuous monitoring of health and environmental conditions is expected to be very helpful in identifying problem at an early stage and taking necessary measures and remedial actions. Analyzing an environment that has complex and highly variable emission sources at appropriate spatial and temporal scales is essential to understanding, monitoring, and controlling the system (1). The environmental condition in which a person lives largely determines the quality of his or her health. Detrimental effects due to increased levels of environmental (air and water) pollution can be mitigated, controlled, or avoided in many cases if early cautionary information is obtained. One cannot overemphasize the need for a reliable monitoring and controlling system for both the environment and health in order to create such a safe and secure situation (2). In this respect, the application of sensor and sensor technology has been playing a significant role. The recently acquired information and the technological capability to precisely engineer material property and behavior have offered opportunities to develop new sensor materials and innovative products, and to meet the demands for novel applications (3). Online sensing of material properties, combined with real-time control, has paved the way to achieving the lofty goals of self-directed and intelligent processing of information. In this regard, there has been a push to adopt the monitoring and controlling of human health and environmental conditions in many real-life problems. The benefits from the successful implementation and operation of such systems could be enormous. Naturally, environmental pollution is of great concern at present because of the imminence of the anticipated negative impact on the climate. This concern is worldwide as environmental pollution cannot be restricted within the boundaries of any country. Due to the rapid development and industrialization occurring globally, large amounts of pollutant gases and other toxic wastes are generated (4). The emission of such gases and the disposal of industrial waste are contributing greatly to increasing levels of pollution in the environment, and consequently the public is exposed to health risks and detrimental effects. Focusing on early detection and the prevention of environmental deterioration can help to mitigate the damages in various aspects of health, thus preventing catastrophic disaster. Recent developments in sensor technology make it possible to monitor personal exposure to air pollutants directly, despite the fact that the activity spaces through which a person is moving have changing concentration fields (5).